Evaluating workplace trust as a construct of worker engagement in construction. Issue 3 (18th March 2019) - Lawani, Kenneth; Hare, Billy; Cameron, Iain
Abstract : This qualitative study developed task-based trust themes and a framework – 'lack of trust', 'ability' (skill, experience and competence), 'benevolence' and 'company integrity' – from interviews based on the perceptions of workers regarding occupational safety and health (OSH) practices. The phenomenological study adopted semi-structured interviews involving engaged workers until saturation. An additional 22 workers participated in validating the trust framework. Findings suggest that no worker perceived lack of trust within their organisations. Two workers perceived their own skill, knowledge and experience and that of other workers to work safely, but considered their organisation to lack genuine care and company integrity. Six workers acknowledged the presence of ability and genuine benevolence within their workplace. However, they identified lack of company integrity from their management regarding OSH practices. Fourteen workers identified ability, genuine benevolence and company integrity qualities and that their management adhere to sets of principles that they find acceptable and consistent. They also recognised their workplaces to have a strong and transparent organisational leadership and integrity. This study of workplace trust, which is part of a wider study, involves the development of a worker engagement maturity model and a prototype digital tool which would be useful for assessing existing workforce engagement towards improving construction OSH practices.